Research progress on the intervention of cognitive function using transcranial alternating current stimulation technology - Wu, Qingchang; Wu, Changli; Liu, Jian (Frontiers in Psychology, 2024)
Transcranial Alternating Current Stimulation (tACS) is a non-invasive brain stimulation that stimulates the cerebral cortex through the output current to regulate neural excitability. This review systematically summarizes the research results of tACS on working memory, learning ability, and decision-making ability, and analyzes the application schemes, safety, and unresolved issues of tACS in the field of cognitive function to provide a theoretical reference for the application of tACS in the field of cognition. Research has found that: (1) tACS intervention can improve the working memory, learning ability, and exercise decision-making ability of athletes and healthy individuals and has a positive effect on improving exercise performance. (2) The factors that determine the effectiveness of tACS intervention include stimulation frequency, stimulation phase, stimulation area, and stimulation dose. The stimulation area and frequency determine which cognitive function tACS affects, whereas the stimulation phase and dose determine the magnitude of the intervention effect. Moreover, before practical application, individual cognitive status, age level, and timing of application should be included in the factors that affect the effectiveness of tACS intervention to develop more scientific intervention plans. (3) Despite the absence of evidence indicating significant safety issues associated with the use of tACS, its widespread adoption among athletes still poses safety risks under the World Anti-Doping Code. In competitive sports, whether the use of tACS will be classified as a “neuro-doping” method leading to disqualification remains uncertain. Therefore, authoritative institutions to provide comprehensive guidelines on the application of tACS, clearly delineating its usage scenarios and defining the safety parameters for tACS stimulation. Additionally, the development of detection devices for tACS usage is essential to ensure that any intervention using tACS can be monitored effectively.